2020
DOI: 10.18410/jebmh/2020/572
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Morbidity and Health Seeking Behaviour among Elderly in a Rural Area of Thrissur District

Abstract: BACKGROUND Elderly people are often neglected in the society particularly with regards to the healthcare service delivery in Indian context. Most of them live with certain forms of morbidities. The consequences of these illnesses in terms of severity affect their willingness to seek help from health care services. Therefore, understanding the morbidities and their health seeking behaviour is a prerequisite for providing essential need-based healthcare services to this marginalised population. A cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…13,14 According to Areekal et al, common reasons for avoiding seeking health treatment include believing the sickness is unimportant or believing it is a normal part of the ageing process. 12 The difference between the findings of this study with that of other previous research could be attributed to the fact that different geographic areas may have different cultural norms, healthcare access, health system delivery, and morbidity patterns. The major strength of the study was that it was conducted as a house-to-house community survey using a pre-structured questionnaire.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…13,14 According to Areekal et al, common reasons for avoiding seeking health treatment include believing the sickness is unimportant or believing it is a normal part of the ageing process. 12 The difference between the findings of this study with that of other previous research could be attributed to the fact that different geographic areas may have different cultural norms, healthcare access, health system delivery, and morbidity patterns. The major strength of the study was that it was conducted as a house-to-house community survey using a pre-structured questionnaire.…”
Section: Discussioncontrasting
confidence: 93%
“…This is consistent with another study from Kerala by B Areekal et al, which indicated that older people are more likely to have diabetes, hypertension, and musculoskeletal conditions. 12 In contrast to these results, a study done in Karnataka by Davalagi et al discovered that respiratory illnesses and musculoskeletal issues were the most prevalent illnesses. 13 Another study conducted in Assam revealed that arthritis and vision impairment are the two most prevalent issues affecting the elderly.…”
Section: Discussionmentioning
confidence: 89%